Research and analysis of regulatory framework and harmonisation of repurposing - Antonio Ivanov; Violeta Getova-Kolarova; Ilko Getov (Pensoft Publishers, 2024)
Drug repurposing is a modern and successful mechanism for discovering new therapeutic indications for authorised medicinal products. There is an absence of a clear definition of the term "drug repurposing" or its synonyms in regulatory frameworks, which clearly shows the need for inclusion and definition of the process. The main regulatory documents show a greater absolute number of repurposing options for European Medicines Agency (EMA) (5) versus Food and Drug Administration (FDA) (4) and the need for harmonisation because of different authorisation procedures and their benefits. While the EU Agency focusses on regulating and improving the interaction between pharmaceutical companies, academia, and non-profit organisations, the U.S. drug regulator directs the generation of candidates for repurposing using digital technologies.